(untitled) (Серія: Історія. Політологія, 2021)
У статті проаналізовано основні нормативні документи, відповідно до яких формується зовнішня політика Республіки Молдова. Розглянуто основні фактори, що впливають на вироблення зовнішньополітичного курсу країни, визначено основні загрози й виклики її суверенітету та територіальній цілісності. Досліджено зміни у декларованих пріоритетах зовнішньої політики Молдови, основну увагу при цьому було зосереджено на двох протилежних її векторах: європейському та євразійському. The article analyzes the main normative documents, according to which the foreign policy of the Republic of Moldova is formed. The main factors influencing the development of the country’s foreign policy are considered. Also the main threats and challenges to the country’s sovereignty and territorial integrity have been identified. Changes in the declared priorities of Moldova ’s foreign policy, especially on the european and eurasian vectors, have been studied. Since declaring independence in 1991, the country has inherited the same problems that are common to most post-Soviet countries, namely: separatism of certain territories, bifurcation of society, some seek to a european future, and others - nostalgia for the Soviet past, economic imbalance , political immaturity and corruption of elites; legal nihilism, etc. This was reflected in the basic documents designed to shape the foreign policy of the republic. The purpose of the study is to analyze the regulatory frameworkof the foreign policy of the Republic of Moldova since independence to the present time, taking into account current trends in international relations. The Constitution, acts that should ensure the functioning system of the national security and defense, the Concept of Foreign Policy of the Republic of Moldova are the main documents governing the country’s foreign policy. Since independence, there have been changes in setting Moldova’s foreign policy priorities. They concerned issues of ensuring the national security of the country, identified threats and challenges facing it. The need for European integration and active participation in the processes of regional political and economic cooperation was recognized. At the same time, the development of a new foreign policy strategy remains relevant, that would meet the current conditions of the international situation, the challenges associated with hybrid threats in the post-Soviet space; would take into account new trends in the relations of the Republic of Moldova with the EU, the USA, etc. At the same time, this document should offer new ways of international assistance in overcoming the country’s socio-economic problems, solving the Transnistrian conflict, and so on.